2016
DOI: 10.5194/essd-8-383-2016
|View full text |Cite
|
Sign up to set email alerts
|

A multi-decade record of high-quality <i>f</i>CO<sub>2</sub> data in version 3 of the Surface Ocean CO<sub>2</sub> Atlas (SOCAT)

Abstract: A new feature is the data set quality control (QC) flag of E for data from alternative sensors and platforms. The accuracy of surface water f CO 2 has been defined for all data set QC flags. Automated range checking has been carried out for all data sets during their upload into SOCAT. The upgrade of the interactive Data Set Viewer (previously known as the Cruise Data Viewer) allows better interrogation of the SOCAT data collection and rapid creation of high-quality figures for scientific presentations. Automa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
402
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 5,811 publications
(411 citation statements)
references
References 102 publications
8
402
1
Order By: Relevance
“…It is also interesting to compare our reported F CO 2 uncertainties to those introduced by the choice of a given pCO 2 product. The application of distinct interpolation techniques in recent years has led to the publication of several global pCO 2 products that are largely based on the same observational dataset (i.e., SOCAT; Bakker et al, 2016). To quantify the uncertainty introduced by the choice of the pCO 2 field, Rödenbeck et al (2015) applied an identical parameterization of the CO 2 exchange at the air-water interface to 14 pCO 2 data products.…”
Section: Discussionmentioning
confidence: 99%
“…It is also interesting to compare our reported F CO 2 uncertainties to those introduced by the choice of a given pCO 2 product. The application of distinct interpolation techniques in recent years has led to the publication of several global pCO 2 products that are largely based on the same observational dataset (i.e., SOCAT; Bakker et al, 2016). To quantify the uncertainty introduced by the choice of the pCO 2 field, Rödenbeck et al (2015) applied an identical parameterization of the CO 2 exchange at the air-water interface to 14 pCO 2 data products.…”
Section: Discussionmentioning
confidence: 99%
“…Emerson, 2014), which may introduce additional constraints for identifying values of a larger number of parameters of plankton ecosystem models. Finally, we point to latest products from compilations and syntheses of oceanic and atmospheric CO 2 data collected by a large international community (Röden-beck et al, 2015;Bakker et al, 2016). Data products like air-sea CO 2 flux of specified ocean regions (biomes), as derived in Rödenbeck et al (2015), in combination with data of nutrient concentrations and O 2 will likely put new light on those parameters that determine variations of the elemental stoichiometry (C : N: P : O 2 ) in model results of inorganic and organic matter cycling.…”
Section: Examples Of Recent Advances In Data Availabilitymentioning
confidence: 99%
“…Laruelle et al (2014) used more than 3 × 10 6 pCO 2 measurements from the SOCATv2 database Bakker et al, 2016 to demonstrate very strong disparities in air-seawater CO 2 exchange at the regional scale and pro-G. G. Laruelle et al: Global coastal pCO 2 maps nounced seasonal variations, especially at temperate latitudes. Furthermore, it was suggested that, despite the presence of a seasonally varying sea-ice cover, Arctic continental shelves are a regional hotspot of CO 2 uptake (Bates et al, 2006;Laruelle et al, 2014;Yasunaka et al, 2016).…”
Section: Introductionmentioning
confidence: 99%